ANALYSIS OF SOLID WASTE MANAGEMENT OF SUGAR INDUSTRY (Studies at The Sugar Industry X In East Java) - Khoiron Khoiron (UNEJ e-Proceeding, 2012)
Sugar industry activities produce large quantities of organic solid waste and byproducts (e.g. leaves from cane, molasses from the final crystallization, bagasse fiber from the cane, and filter cake), fly ash, and bottom ash. Solid waste has potential to pollute the enviornment and negative impact to public health. The study aim to analyze management of solid waste fromsugar industry. This research design was descriptive obsevation approach. Filter cake is usually used by nearby farmers as organic fertilizer although in some cases its application as organic fertilizer is preceded by biocomposting. Bagasse is used as fuel for boilers. It is estimated that 70% of the power requirements of sugarmills is fulfilled in this way. Bagasse is also used for chip-board and paper manufacture.